Implementasi Sistem CRM Meningkatkan Kepuasan Customer Pada Divisi Business Center Bina Nusantara - Alfianto Alfianto; Hin, Lauw Li (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
In the continuously evolving digital era, organizations are required to optimize information technology to improve service quality and strengthen customer relationships. The Business Center Division faces various challenges, such as delays in handling complaints, suboptimal recording of customer interactions, and conventional service processes, which lead to decreased service effectiveness and customer satisfaction levels. Therefore, a solution is needed in the form of a Customer Relationship Management (CRM) system capable of integrating customer data management, improving communication quality, and supporting fast, accurate decision-making. This study aims to design and implement a CRM system within the Business Center Division to enhance customer satisfaction and organizational operational efficiency. The research methodology includes system requirements analysis, system design, application development, implementation, and performance evaluation post-deployment. The developed CRM system is designed to support the recording of service activities, centralized customer data management, systematic monitoring and handling of complaints, and the provision of relevant reports and information for management. The results indicate that the implementation of the CRM system improves service quality through more structured and well-documented work processes, accelerates response times to customer needs and complaints, facilitates information access, and enhances inter-departmental coordination. The application of CRM also has a positive impact on employee efficiency and helps the organization build better long-term relationships with customers. Thus, the implementation of a CRM system in the Business Center Division is proven to be an effective solution for increasing customer satisfaction, improving business processes, and supporting organizational competitiveness amidst an increasingly competitive and service-oriented business environment.